The Role of β Cell Stress and Neo-Epitopes in the Immunopathology of Type 1 Diabetes - Piganelli, Jon D.; Mamula, Mark J.; James, Eddie A. (Frontiers in Endocrinology, 2021)
Due to their secretory function, β cells are predisposed to higher levels of endoplasmic reticulum (ER) stress and greater sensitivity to inflammation. These stresses elicit changes in β cells that alter their function and immunogenicity, including defective ribosomal initiation, post-translational modifications (PTM) of endogenous β cell proteins, and alternative splicing. Multiple published reports confirm the presence of not only CD8+ T cells, but also autoreactive CD4+ T cells within pancreatic islets. Although the specificities of T cells that infiltrate human islets are incompletely characterized, they have been confirmed to include neo-epitopes that are formed through stress-related enzymatic modifications of β cell proteins. This article summarizes emerging knowledge about stress-induced changes in β cells and data supporting a role for neo-antigen formation and cross-talk between immune cells and β cells that provokes autoimmune attack - leading to a breakdown in tissue-specific tolerance in subjects who develop type 1 diabetes.